Preconditioning of thin‐film PV module technologies for calibration. (9th July 2012) - Kenny, Robert P.; Chatzipanagi, Anatoli I.; Sample, Tony
ABSTRACT Thin‐film module technologies are known for their metastability, and a study of this behaviour for different types of thin‐film modules is presented. The modules investigated through a series of controlled light‐soaking procedures are copper–indium sulfide (CIS), copper–indium–gallium diselenide (CIGS), cadmium telluride (CdTe), triple‐junction amorphous silicon (a‐Si), micromorph silicon (a‐Si/μ‐Si) and thin‐film crystalline silicon (CSG). The objective of the paper is to investigate whether after the stabilization point, as defined in the international qualification standard IEC 61646, there is any further significant change in the maximum power of the module. It was found that all CIS and CIGS modules investigated in this study stabilize according to IEC 61646, and no further significant change in maximum power is observed. The same result was obtained also for the CSG module. To the contrary, CdTe, triple‐junction a‐Si and a‐Si/μ‐Si modules continued to show further change in maximum power even after they stabilize according to IEC 61646. For the purposes of module qualification, given the need to stay 'within reasonable constraints of cost and time', the stability procedure of IEC 61646 could be considered as satisfactory. However, in order to perform sufficient preconditioning of thin‐film modules prior to precision calibration, a new more complete standard procedure is needed, tailored to the specific technology. For example, tighter stability limits lower than the current 2%, which would have the effect of increasing the number of light‐soaking periods required. Copyright © 2012 John Wiley & Sons, Ltd.